2017
DOI: 10.32607/20758251-2017-9-1-56-67
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Morphological Heterogeneity of Breast Cancer As an Indicator of the Metastatic Potential and Tumor Chemosensitivity

Abstract: Breast cancer (BC) demonstrates considerable intratumoral morphological heterogeneity. The aim of this work was to evaluate the relationship among different morphological structures, the rate of metastasis, and efficacy of neoadjuvant chemotherapy (NAC) in NAC-treated (n = 427) and NAC-naïve (n = 249) BC patients. We also studied the involvement of an epithelial-mesenchymal transition (EMT) in the development of the intratumoral morphological heterogeneity of BC. We found a significant association between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…A poor response to NAC is associated with the presence of alveolar, trabecular, or discrete groups in breast tumors, while the association was more significant in premenopausal patients. In contrast, a good response to chemotherapy was found in BCs with solid structures [2].…”
Section: Different Morphological Structures Of Breast Tumors Demonstrmentioning
confidence: 86%
See 1 more Smart Citation
“…A poor response to NAC is associated with the presence of alveolar, trabecular, or discrete groups in breast tumors, while the association was more significant in premenopausal patients. In contrast, a good response to chemotherapy was found in BCs with solid structures [2].…”
Section: Different Morphological Structures Of Breast Tumors Demonstrmentioning
confidence: 86%
“…Such intratumor morphological heterogeneity is a common phenomenon in IC NST. Up to 80% of IC NST shows the presence of 3-5 different types of morphological structures [2].…”
Section: Different Morphological Structures Of Breast Tumors Demonstrmentioning
confidence: 99%
“…Furthermore, the mixture of cancer nests with these different histologies has frequently been reported, and the pattern of stromal distribution in histologically mixed tumors is generally heterogeneous. Previous studies reported that the heterogeneity of stromal distribution in pathological ndings has potential as a prognostic marker [10,11], suggesting that the outcomes of patients may be estimated in the pre-operative setting by evaluating the cancer stromal pattern indirectly using imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identi ed stromal heterogeneity as a prognostic or therapeutic biomarker, and showed that a heteronomous stromal pattern in pancreatic and breast cancers correlated with a poor outcome [10,11]. The tumor stroma ratio is used as a prognostic marker in gastric and colon cancers [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…show that these EMT stimulators are also closely correlated with metastasis and chemoresistance in breast cancer. 32,33 Interestingly, recent studies show that overexpression of EMT stimulators is caused by the downregulation of tumor suppressor miRNAs. 34,35 In the present study, for the first time, we found that miR-708-3p negatively regulates EMT in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%